Pelaksanaan Ranah Afektif pada Pembelajaran PAI Kelas VIII di SMPN 3 Tigo Nagari Kabupaten Pasaman - Rahmiati Rahmiati; Wedra Aprison; Hamdi Abdul Karim (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This research is motivated by the PAI learning process which prioritizes material rather than attitudes. In this case, the teacher has tried to implement the affective domain approach in PAI learning, but in reality there are still problems regarding students' affective domain in PAI learning. This can be seen from the attitude of students who pay less attention to the teacher when explaining the lesson, such as students talking to their classmates about other things, singing in class, and often excusing themselves during the learning process. The aim of this study is to look at the implementation of the Affective Domain in PAI Learning through a teacher approach. The type of research is descriptive-qualitative, the main informant for this research is an Islamic Religious Education Teacher who teaches in class VIII C, and the supporting informants are students in class VIII C. Data collection techniques use observation, interviews and documentation. Data analysis techniques use data reduction, data presentation and data verification. To test the validity of the data by using data triangulation, namely comparing the results of interviews conducted by key informants with supporting informants and the results of direct observations. The results of this research show that the implementation of the affective domain in PAI learning is through an approach by teachers in the affective domain in Class VIII C of SMPN 3 Tigo Nagari, Pasaman Regency using an experiential approach by teaching knowledge through experience on Sunnah prayer material, the Habituation Approach provides the habit of reading the Al-Qur 'an together before starting learning, the teacher exemplifies the exemplary approach first to the students regarding respect and obedience to parents and teachers before taking the exemplary approach.